Iceland : 2022 Article IV Consultation - Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Iceland's economy has weathered multiple shocks since 2019 relatively well. The economic outlook is positive but suggests long-term scarring. The risks are tilted to the downside and are associated with the global impact of a potential escalation in the war in Ukraine, the pandemic, economic disruptions, and tighter global financial conditions. On the upside, tourism and new innovative industries could help the economy recover faster.